Orthopaedic biomechanics madeeasy - Malik, Sheraz S.; Malik, Shahbaz S. (Cambridge : Cambridge University Press, 2015)
Orthopaedic surgeons require not only an understanding of anatomy and clinical sciences, and competence in surgical skills, but also a strong foundation in biomechanics. The application of biomechanics plays an increasing role in modern orthopaedics; for example, correct decisions about the mode of treatment and choice of implants are just as important as operating precisely to reach a specific anatomical landmark. This book simplifies the core principles in orthopaedic biomechanics, giving readers the solid grounding they need to flourish in the specialty. Each topic is covered in a discrete, double-page spread, featuring concise text accompanied by illustrations or tables to give readers a solid understanding of the concepts discussed. This is a must-read guide for orthopaedic trainees at every level, and will be valuable for biomechanical researchers and other professionals in the field.
Title from publisher's bibliographic system (viewed on 13 May 2016).
Keywords: Musculoskeletal Physiological Phenomena; Biomechanical Phenomena